E-government in the making: an actor network perspective - Antonio Cordella and Jakob Hesse (Transforming Government: People, Process and Policy, 2015)
Abstract Purpose – This paper aims to introduce a new approach to the framing of e-government projects. It discusses e-government as a continuing process of interaction and change. The paper uses general concepts borrowed from actor–network theory (ANT) to highlight the on-going negotiation that is an endogenous characteristic of every e-government projects. Design/methodology/approach – The research builds on the findings of a case study. The case of the Akshaya e-government project in Kerala, India, is presented to offer an instance of the negotiation that occurs among the different actors involved and the consequent changes the project itself experiences. Findings – The paper shows that e-government initiatives are unstable and change over time, as they are cast in the dynamic interaction that occurs between the actors involved in the e-government project. It also suggests that the ANT is a valuable framework to study these dynamics. Research limitations/implications – Main contribution of the paper is the evidence that e-government projects should be studied in their making and not as a result of planned action and sequential evolutionary phases. Practical implications – The paper offers new insights for the planning, design and most importantly management of e-government projects. Originality/value – The paper contributes to the literature by shedding light on the importance of the dynamic interactions that shape the impact of information and communication technologies (ICTs) on government policies. The proposed framework is a basis for further theorisation with regards to the complexity underpinning the deployment of ICTs in the public sector.